Desenvolvimento de um método para levantamento de tecnologias de materiais empregados no trem de força automotivo (powertrain) a partir de patentes - Rocco, Giordanno Coscelli (Universidade Federal de São Carlos, 2012)
This research approaches the study from patents of technologies for materials used in power train of motor vehicles, to provide additional information in order to support decision making in this universe, especially in the selection of materials and their processing. The powertrain is currently the most important subsystem in a car, being appointed as chief in the changes and technological developments that will happen in the context of the automotive industry. In this sense, the technologies of materials and their processing, and methods of selection of the latter assume a key role as a vector for change, providing alternatives that meet the new demands and challenges set by the consumer market and regulations, such as: Cost reduction; Weight Reduction (for fuel economy) Environment (fuel economy, reduced emissions, alternative fuels, recycling); Security; Comfort; Customization / variability, and product(s) design. To raise and analyze technical information on materials and its correlation with the market, and their trends, it was used the techniques of technological forecasting and competitive intelligence, and the analysis of patents as the primary tool, aided by the use of specific treatment information software, bibliometric analysis and content analysis. There was emphasis on materials involving low density, good mechanical properties, and good performance in relation to surface phenomena and wear, such as lubricants, aluminum, steel, ceramics, polymers, composites, nanotechnology, among others. Were investigated in more detail the technologies involving aluminum and magnesium, it was possible to identify an emphasis on processing techniques involving surface coating and casting. As for the biggest depositors of patents, the focus is for companies like General Electric, Nippondenso, and Japanese automakers like Toyota, Nissan, Honda and Mitsubishi.
Devolopment of a patent based method for surveying materials technologies used in automotive powertrain
Keywords: Engenharia de materiais; Patentes; Seleção de materiais; Prospecção tecnológica; Inteligência competitiva.; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA